2013
DOI: 10.1080/09540121.2013.793278
|View full text |Cite
|
Sign up to set email alerts
|

Task shifting of HIV management from doctors to nurses in Africa: Clinical outcomes and evidence on nurse self-efficacy and job satisfaction

Abstract: With 24% global disease burden and 3% global health workforce, the World Health Organization (WHO) designates the African region a critical workforce shortage area. Task shifting is a WHO-recommended strategy for countries with severe health worker shortages. It involves redistribution of healthcare tasks to make efficient use of available workers. Severe physician shortages, increasing HIV disease burden, and the need for improved access to antiretroviral treatment (ART) posed serious challenges for Africa. S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
40
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(43 citation statements)
references
References 33 publications
3
40
0
Order By: Relevance
“…Twelve percent of the district M&E Officer posts were vacated during the first year, with low job satisfaction as the main factor. This is in-line with findings from a recent literature review of studies in Africa investigating the shifting of tasks from physicians to nurses that found that job satisfaction was closely related to staff retention and important for sustainability [23]. Given that the capacity development activities for this new cadre were based on the incremental building of skills, retaining staff was especially important.…”
Section: Discussionsupporting
confidence: 83%
“…Twelve percent of the district M&E Officer posts were vacated during the first year, with low job satisfaction as the main factor. This is in-line with findings from a recent literature review of studies in Africa investigating the shifting of tasks from physicians to nurses that found that job satisfaction was closely related to staff retention and important for sustainability [23]. Given that the capacity development activities for this new cadre were based on the incremental building of skills, retaining staff was especially important.…”
Section: Discussionsupporting
confidence: 83%
“…Potential benefi ts of task shifting include increased coverage, more efficient use of available healthcare staff and utilization of local staff who are familiar with locally used expressions and presentations of mental distress, with a reduction of stigma (Kagee et al, 2013;van Ginneken et al, 2013). Barriers to a task sharing approach include the signifi cant rates of staff turnover in many primary healthcare settings, the requirement of substantial training and supervision, and the risk of ' task dumping ' (overloading primary health workers with tasks they cannot reasonably perform well) Iwu & Holzemer, 2014). There is now broad international consensus around the critical need to train non-specialist health workers, in low-and middle-income settings, in diagnosing and managing mental disorders .…”
Section: Task Shifting and Task Dumpingmentioning
confidence: 99%
“…In Thailand, HIV-infected patients exposed to a nurse-led primary care service reported greater satisfaction with services than their counterparts who continued to be seen by physicians. 22 Iwu and Holzemer 23 reviewed studies of physician-to-nurse task shifting in HIV settings in Sub-Saharan Africa; they reported increased levels of job satisfaction, as indicated by feelings of stature, achievement, and morale among nurses in 3 studies. In Malawi, patients rated HIV prevention services more positively after the hospital workers (including physicians) received training in delivering peer-led HIV prevention interventions.…”
Section: Discussionmentioning
confidence: 99%
“…17,1921 Fewer studies have focused on the impact of task shifting on patient satisfaction with clinical services and the satisfaction of the lower-cadre workers with their new positions. 13,22,23 …”
Section: Introductionmentioning
confidence: 99%